Bifidobacterium adolescentis as a key member of the human gut microbiota in the production of GABA - Duranti, Sabrina (Sci Rep, 2020)
Gamma aminobutyric acid (GABA) is the principal inhibitory neurotransmitter playing a key role in anxiety and depression disorders in mammals. Recent studies revealed that members of the gut microbiota are able to produce GABA modulating the gut–brain axis response. Among members of the human gut microbiota, bifidobacteria are well known to establish many metabolic and physiologic interactions with the host. In this study, we performed genome analyses of more than 1,000 bifidobacterial strains publicly available revealing that Bifidobacterium adolescentis taxon might represent a model GABA producer in human gastrointestinal tract. Moreover, the in silico screening of human/animal metagenomic datasets showed an intriguing association/correlation between B. adolescentis load and mental disorders such as depression and anxiety. Interestingly, in vitro screening of 82 B. adolescentis strains allowed identifying two high GABA producers, i.e. B. adolescentis PRL2019 and B. adolescentis HD17T2H, which were employed in an in vivo trial in rats. Feeding Groningen rats with a supplementation of B. adolescentis strains, confirmed the ability of these microorganisms to stimulate the in vivo production of GABA highlighting their potential implication in gut–brain axis interactions.